Factors Associated with Anemia Among Pregnant Women attending Arif Memorial Teaching Hospital, Lahore - Saima Qurban, Asma Yasin, Samar Hussain, Madiha Afzal, Huma Tahseen, Ayesha Azhar Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anemia in pregnancy is a major contributor that leads to severe morbidity and even high risk for maternal mortality. There is lack of information about factors that lead to anemia, especially in low-income countries. Objective: To determine the frequency of factors associated with anemia among pregnant women attending a tertiary care hospital, Lahore Material and methods: This cross sectional study was one at Department of Obstetrics & Gynecology for 6 months from 1st October 2021 to 1st March 2022. One hundred females were enrolled and their medical records and history was taken to determine the factors involved in anemia during pregnancy. All the data was analyzed in SPSS v26. Results: In this study, the mean age of females was 28.61 ± 6.45 years. The mean gestational age at presentation was 35.02 ± 2.17 weeks. The mean age at first pregnancy was 22.76 ± 4.79 years. The mean birth interval was 7.39 ± 3.92 months. Out of 100 females, the most common factor was inter-pregnancy interval <6 months [48 (48%)], followed-by 72 (72%) not taken folic acid, 86 (86%) of not taking iron supplement, 44 (44%) were taking grains only, 50 (50%) were taking vegetables only, 41 (41%) were taking meat >2 times per week, 64 (64%) were not taking fruits, 69 (69%) were not taking milk, 57 (57%) were avoiding food or taking less meals, 61 (61%) had nausea and vomiting during pregnancy and 38 (38%) had chronic anemia (before pregnancy). Conclusion: In this study, all of the above factors were highly effective in occurrence of anemia in pregnancy.